Building Innovative Online Korean and Japanese Courses: A Pilot on Technology- Enhanced Curriculum Development - Sato, E.; Sohn, H.; Chen, Julian; Adebowale, K.; Jourdain, S. (Sage, 2015)
Our pilot project created blended/online courses to accommodate the growing needs of precollegiate and collegiate students interested in learning Korean and Japanese. In the initial phase, we conducted a survey of students’ experiences with and perceptions about blended/online Asian language learning. We found a general lack of familiarity with, and moderate resistance toward, online language learning modes. With learner attitudes in mind, we developed online modules for beginning Korean and Japanese courses. In this article, we report the survey results and the process of developing these innovative blended and online modalities of content delivery, focusing on the strengths of the modules and the unforeseen development challenges. The impacts that these technology-enhanced environments may have on student perceptions of transactional distance and tele-/copresence are explored. We suggest that transforming conventional East Asian language courses into blended/online modes is not only feasible but also beneficial for foreign language teaching and learning.